509 Late-Breaking: Effect of a Sensory Additive on Sow Reproductive Performance. (8th October 2021) - Davis, Nathan; Tsia, Tsungcheng; Bass, Benjamin; Tedo, Gemma; Morais, Sofia; Maxwell, Charles
Abstract: The addition of a sensory additive to sow diets during the summer improved feed intake during lactation, and litter performance. The aim of this study was to evaluate the impact of the sensory additive on sow lactation performance during cooler temperatures. Three consecutive groups (n = 61 total) of sows were farrowed during winter (October, December and January). Sows were weighed, and back fat depth was measured, at 110 d of gestation prior to entering the lactation room, and again at weaning. The sows were sorted by parity, and then allotted by BW at d 110 to Control or 0.075% sensory additive (Luctamax® SowVive, Lucta S.A., Spain). Experimental diets were offered upon entry to the lactation room and fed through weaning. Feed disappearance was recorded every three days. Sows were fed 2.72 kg/head/day until farrowing, and then allowed to eat ad libitum from 24 hours post-farrowing until weaning. Data were analyzed using the PROC MIXED procedure of SAS as an RCBD with treatment as the fixed effect and group as a random effect. No differences were observed on sows feed intake (P > 0.4), 10 th rib backfat thickness change (P = 0.632) and body weight change from d 110 of gestation to weaning (P = 0.65, Table 1). Sows fed the sensory additive lowered preweaning mortality by 4.9% (P = 0.051), and weaned an additional 1.42 piglets (P = 0.026) with similar weaning weights (P = 0.86) when compared to control. In conclusion, in the current study, lactation diets supplemented with a sensory additive improved litter performance and helped maintain sow body condition.